Design and analysis of a modified segmented cladding fiber with parabolic-profile core. (5th February 2018) - Ma, Shaoshuo; Ning, Tigang; Pei, Li; Li, Jing; Zheng, Jingjing
Abstract: A novel segmented cladding fiber structure is proposed in this paper for large-mode area properties. In this structure, a parabolic-profile core is surrounded by segmented cladding. It is called parabolic-profile core segmented-cladding fiber. The novel fiber has a better single-mode operation than segmented-cladding fiber. A large effective area of 980 µ m 2 is achieved. It is found that the effective-mode area does not vary with the changing of the bending radius. The bending performance does not change with varying the bending orientation.